2009
DOI: 10.14710/jitaa.34.4.289-294
|View full text |Cite
|
Sign up to set email alerts
|

MULTIVARIATE ANALYSIS ON PHENOTYPIC TRAITS OF BODY MEASUREMENT IN SWAMP BUFFALO ( Bubalus bubalis)

Abstract: The objective of this research was to study the relationship between body measurement and body weight and closeness among swamp buffalo at three populations in Central Java. The 110 heads of swamp buffalo measured were from 29 heads of Pati district, 56 heads of Kudus district, and 25 heads of Semarang city. Age of buffaloes used was 1-5 years old. The quantitative traits measured were body weight ( BW), body length (BL), shoulder height (SH), pelvic height (PH), chest depth (CD), chest circumference (CC), che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 4 publications
1
12
2
Order By: Relevance
“…However, by using the same analysis Salamena et al (2007) showed that the Kisar sheep in Maluku had not yet established a new sub-population. Similar results were also shown for Central Java local buffalo (Johari et al, 2009) and Maluku local buffalo (Salamena and Papilaja, 2010), several sub-populations were observed could not be differentiated and therefore had not formed a new sub-population.…”
Section: Resultssupporting
confidence: 84%
“…However, by using the same analysis Salamena et al (2007) showed that the Kisar sheep in Maluku had not yet established a new sub-population. Similar results were also shown for Central Java local buffalo (Johari et al, 2009) and Maluku local buffalo (Salamena and Papilaja, 2010), several sub-populations were observed could not be differentiated and therefore had not formed a new sub-population.…”
Section: Resultssupporting
confidence: 84%
“…Both regions are geographically adjacent to each other. Therefore, free migration and mating can occur between both nearby populations (Johari et al 2009). The genetic relationships between the buffalo groups are consistent with their biogeographic origins (Winaya et al 2019).…”
Section: Phenotypic Relationships Between Indigenous Buffaloes From Bmentioning
confidence: 68%
“…Due to their near geographic position, two or more populations can be grouped into a single cluster (Abinawanto et al 2018). Johari et al (2009) stated that all buffaloes from the nearest regions showed the same position based on canonical structures. This is related to the genetic relationship of the buffaloes, which were assumed to originate from the same ancestor by marriage.…”
Section: The Correlation Between Each Morphometric Characteristics Ofmentioning
confidence: 99%
“…Yakubu (2010) attributed the varying correlation coefficients between the morphological traits of male and female Yankasa sheep to sex differences in the genetic architecture of the animals. Sexual dimorphism in phenotypic relationships in buffalo had also been reported (Johari et al 2009). …”
Section: Resultsmentioning
confidence: 92%